Organic arsenical exposures stimulates atheroscleorosis through oxidative stress increase and adhesion molecule expression - Ishola, Afeez Adenkule; A Talib, Noorlelawati; Muhammad, Siti Aeshah @ Naznin; Buyong, Zunariah; Mohamed, Abdul Hadi; Myint, Yi Yi; Samsuddin, Niza; Abdul Ghani, Radiah; Abdullah, Norzamzila (World association of Medical Editors, 2016)
Approximately 100 million people are exposed to arsenic worldwide, majorly through drinking water and anthropogenic activities. Monosodium methylarsonate (MSMA) is a potent organoarsenical content of herbicides used in many Asian countries. Epidemiological studies have linked inorganic arsenic exposure with atherosclerosis, whereas organoarsenicals toxicological studies are scanty. Paraoxonase 1 (PON1) enzyme suppresses systemic Ox-LDL generation, thereby preventing atherosclerosis. We investigated effects of MSMA oral exposure on PON1, lipid peroxidation and atherosclerosis development. Five groups (n=11) of Sprague- Dawley rats received daily intubation of MSMA at 0 (control), 42.1, 63.2, 126.4 and 210.7 mg/kg BW respectively for 16 weeks. Serum samples were analysed for PON1 activities, Ox-LDL and MDA levels. Histomorphometric evaluation (H&E and VVG) and immunohistochemistry (VCAM-1 and ICAM-1) were done on aorta. High mortality rate led to discontinuation of 126.4 and 210.7 mg/kg BW treatment groups. Groups treated with 42.1 and 63.2 mg/kg B.W. MSMA had a significantly higher MDA (p=0.004,CI: 2.73-0.82) and Ox-LDL (p<0.0001,CI: 2425.07-955.45) levels but lower PON1:Ox-LDLratio (p<0.0001,CI: 0.49-1.07) compared to control. Microscopically, treatment groups showed early atherosclerotic intima thickening and positive VCAM-1 and ICAM-1 expressions. In conclusion, chronic MSMA exposure reduced PON1 ability to hydrolyse Ox-LDL and also induced inflammation by elevating oxidative stress that supports early atherosclerosis development.